Akuntansi untuk Organisasi Siswa - Yosia Pratama Sirait; Jasinda Arba Lestari; Fathimattuzahro; Nazwa Agnes Hilyatul Ummah; Irenne Putren (Universitas Pamulang, 2025)
Many student organizations at the high school level still have financial reports that cannot be considered well-prepared, both in terms of recording, management, and presentation of financial information. We also want to see whether this condition is also found in student organization at SMA Negeri 11 Tangerang Selatan, where there is still a lack of understanding regarding systematic and standardized financial reporting based on simple accounting principles. The main problem faced by the organitation in this community service activity is the absence of proper evaluation and guidance on their financial reports, making it necessary to provide assistance in the process of preparing and writing them. The purpose of this activity is to enhance the ability of student organizations to prepare financial reports that are accurate, transparent, and accountable. The method used is socialization through training sessions on basic financial reporting, including transaction recording, cash book preparation, and final report presentation. The results of this program indicate an improvement in the students’ knowledge and understanding of proper financial report writing. Keywords: financial report, student organization, socialization